2010
DOI: 10.1093/gbe/evq020
|View full text |Cite
|
Sign up to set email alerts
|

More Functional V1R Genes Occur in Nest-Living and Nocturnal Terricolous Mammals

Abstract: Size of the vomeronasal type 1 receptor (V1R) gene repertoire may be a good indicator for examining the relationship between animal genomes and their environmental niche specialization, especially the relationship between ecological factors and the molecular evolutionary history of the sensory system. Recently, Young et al. (Young JM, Massa HF, Hsu L, Trask BJ. 2009. Extreme variability among mammalian V1R gene families. Genome Res.) concluded that no single ecological factor could explain the extreme variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
(54 reference statements)
1
20
0
Order By: Relevance
“…Shifts in vomeronasal receptor repertoires have been associated with adaptations to different habitats and/or life histories, as well as to the development of social structures (Grus et al 2005, 2007; Young et al 2005; Young and Trask 2007; Wang et al 2010). Our study opens new perspectives for the exploration of vomeronasal receptor repertoires in Sauropsida reptiles, a group for which an increasing number of new model species are being developed (Milinkovitch and Tzika 2007; Tzika and Milinkovitch 2007) and genomic/transcriptomic data are emerging (Schwartz et al 2010; Alfoldi et al 2011; Castoe et al 2011; Tzika et al 2011; St John et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Shifts in vomeronasal receptor repertoires have been associated with adaptations to different habitats and/or life histories, as well as to the development of social structures (Grus et al 2005, 2007; Young et al 2005; Young and Trask 2007; Wang et al 2010). Our study opens new perspectives for the exploration of vomeronasal receptor repertoires in Sauropsida reptiles, a group for which an increasing number of new model species are being developed (Milinkovitch and Tzika 2007; Tzika and Milinkovitch 2007) and genomic/transcriptomic data are emerging (Schwartz et al 2010; Alfoldi et al 2011; Castoe et al 2011; Tzika et al 2011; St John et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These comparisons do not, however, provide definitive evidence that expanded V1R 233 repertoires in primates are strictly associated with nocturnal life history (Wang et al 2010; hypothesis that a nocturnal life history alone is sufficient for explaining V1R elaboration in 239 mouse lemurs. Though it is true that both aye-aye and tarsier have more V1R copies than the 240 diurnal primates compared here, they also show a high proportion of putative pseudogenes and 241 an absence of some V1R subfamilies found in Cheirogaleidae ( Figure 1A and B).…”
Section: Tarsius) Species Have Repertoires With Low Percentages Of Inmentioning
confidence: 86%
“…The result of such analyses (comparative genomics and gene ontology analyses) is typically a list of processes or functions (for example metabolic pathways) that are significantly associated with, for example, nocturnality. For example, many comparative genomics studies have revealed a higher diversification of the olfactory receptors repertoire [18,32,50]. Although this is an expected biological trait, the unbiased result of comparative genomics offers further support to the importance of olfaction in low-light environments.…”
Section: Le Duc and T Sch€ Onebergmentioning
confidence: 99%